International Committee on Systematics of Prokaryotes: Subcommittee on the Taxonomy of Aerobic Bacteroidetes (formerly Flavobacterium and Cytophaga-like bacteria). Issue 11 (28th November 2020) - Bowman, John P.; Bernardet, Jean-Francois; Frandsen Lau, Ellen
Abstract : Minutes of the meeting: 15 November 2017 (Skype meeting).